2015
DOI: 10.1088/0031-9155/60/3/1047
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of three commercially available metal artifact reduction methods for CT imaging

Abstract: Three commercial metal artifact reduction methods were evaluated for use in computed tomography (CT) imaging in the presence of clinically realistic metal implants: Philips O-MAR, GE's monochromatic Gemstone Spectral Imaging (GSI) using dual-energy CT, and GSI monochromatic imaging with metal artifact reduction software applied (MARs). Each method was evaluated according to CT number accuracy, metal size accuracy, and streak artifact severity reduction by using several phantoms, including three anthropomorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 31 publications
(53 reference statements)
14
192
1
1
Order By: Relevance
“…The measured doses at depths were compared with dose calculations by collapsed cone convolution (CCC) algorithm in Pinnacle TPS with a dose grid of 1 × 1 × 1 mm 3 . Although there are more accurate dose algorithms 27 that can be used to reduce metal artifact and calculate dose around high‐density heterogeneities, the CCC algorithm was chosen because it is the default and also the most accurate dose algorithm used by Pinnacle and the purpose of this study was to calibrate the Pinnacle TPS to accurately calculate dose around the metallic port. The density in the TPS model of the metallic port was adjusted with an extended CT conversion table in Pinnacle until the calculation results agreed with the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The measured doses at depths were compared with dose calculations by collapsed cone convolution (CCC) algorithm in Pinnacle TPS with a dose grid of 1 × 1 × 1 mm 3 . Although there are more accurate dose algorithms 27 that can be used to reduce metal artifact and calculate dose around high‐density heterogeneities, the CCC algorithm was chosen because it is the default and also the most accurate dose algorithm used by Pinnacle and the purpose of this study was to calibrate the Pinnacle TPS to accurately calculate dose around the metallic port. The density in the TPS model of the metallic port was adjusted with an extended CT conversion table in Pinnacle until the calculation results agreed with the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Our phantom study was conducted with the Catphan® 504 phantom to evaluate the impact of MAR algorithm on CT number sensitometry, geometric accuracy, The dimension of the stainless steel insert was also measured on the CT image by identifying the metal pixel using a threshold HU value (half the maximum metal HU value) [15]. An average value taken from the lateral and vertical directions of the stainless steel rod on central axis was compared to the physical dimension measured with an electronic caliper.…”
Section: Evaluation Of Image Quality On Phantomsmentioning
confidence: 99%
“…In addition, dual energy CT has been shown to be effective in reducing metal artifacts [11]. Some commercial products [11] [12] [13] [14] [15] have become available in the recent years due to the increasing computing power.…”
mentioning
confidence: 99%
“…The same study noted that the wide variance of tissue density in the thorax at lung, bone and soft tissue interfaces contributed to increased distant streak artefact. 19 Jeong et al 20 showed improved image quality in the context of spinal and hip joint prostheses compared with standard iterative reconstruction without IMART. Clinically, IMART has been shown to be beneficial for structure delineation and dosimetry in the planning of pelvic radiotherapy in patients with hip joint prostheses 21 and does not affect spinal stereotactic body radiation therapy treatment planning.…”
Section: Hardware Techniquesmentioning
confidence: 99%